Numerical simulation of trickle bed reactors for biological methanation. (23rd November 2020) - Markthaler, Simon; Plankenbühler, Thomas; Weidlich, Tobias; Neubert, Michael; Karl, Jürgen
Graphical abstract: Highlights: Implementation of a CFD model based on the Eularian-Eularian method. Experimental data of the hydrodynamics, in particular liquid dispersion and holdup. Good agreement of simulation and experiments with regard to averaged macroscopic fluid flow. Spatial prediction of species adsorption and methane production. Abstract: Biological methanation in trickle bed reactors is an auspicious approach to convert hydrogen and carbon dioxide into methane. In order to analyze this process, a comprehensive CFD model was implemented including multiphase flow, absorption, and reaction phenomena. The model is based on the Eulerian-Eulerian method. Experimental investigations and literature data serve as its validation. The experiments focused on the hydrodynamics of a trickle bed composed of clay granulate and the applied reactor enabled detailed measurements of radial liquid flow profiles and liquid holdup dependent on the overall volume flow rate. The simulation of liquid dispersion confirms the experimental results regarding averaged macroscopic fluid flow. However, liquid holdup is slightly underestimated by the computational model. In addition to the hydrodynamic investigation, simulation of biological methanation provide insight into mutual interactions between multiphase flow and biochemical conversion and present a methane production rate on the same order of magnitude as literature values.